Photovoltaics with Ferroelectrics: Current Status and Beyond. Issue 26 (2nd May 2016) - Paillard, Charles; Bai, Xiaofei; Infante, Ingrid C.; Guennou, Maël; Geneste, Grégory; Alexe, Marin; Kreisel, Jens; Dkhil, Brahim
Abstract : Ferroelectrics carry a switchable spontaneous electric polarization. This polarization is usually coupled to strain, making ferroelectrics good piezoelectrics. When coupled to magnetism, they become so‐called multiferroic systems, a field that has been widely investigated since 2003. While ferroelectrics are birefringent and non‐linear optically transparent materials, the coupling of polarization with optical properties has received, since 2009, renewed attention, triggered notably by low‐bandgap ferroelectrics suitable for sunlight spectrum absorption and original photovoltaic effects. Consequently, power conversion efficiencies up to 8.1% were recently achieved and values of 19.5% were predicted, making photoferroelectrics promising photovoltaic alternatives. This article aims at providing an up‐to‐date review on this emerging and rapidly progressing field by highlighting several important issues and parameters, such as the role of domain walls, ways to tune the bandgap, consequences arising from the polarization switchability, and the role of defects and contact electrodes, as well as the downscaling effects. Beyond photovoltaicity, other polarization‐related processes are also described, like light‐induced deformation (photostriction) or light‐assisted chemical reaction (photostriction). It is hoped that this overview will encourage further avenues to be explored and challenged and, as a byproduct, will inspire other research communities in material science, e.g., so‐called hybrid halide perovskites. Abstract : The conversion of light into electricity in piezoelectrics originates from their intrinsic inversion symmetry breaking. This photovoltaic effect, the underlying microscopic mechanisms, and the influential parameters are reviewed in ferroelectrics, which are characterized by a switchable spontaneous polarization.